2017
DOI: 10.2196/cancer.6996
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-Based Patient-Reported Outcomes: Willingness, Needs, and Barriers in Adjuvant and Metastatic Breast Cancer Patients

Abstract: BackgroundPatient-reported outcomes (PROs) play an increasingly important role as an adjunct to clinical outcome parameters in measuring health-related quality of life (HRQoL). In fact, PROs are already the accepted gold standard for collecting data about patients’ subjective perception of their own state of health. Currently, paper-based surveys of PRO still predominate; however, knowledge regarding the feasibility of and barriers to electronic-based PRO (ePRO) acceptance remains limited.ObjectiveThe objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 54 publications
5
69
1
13
Order By: Relevance
“…The first part focused on the patientsʼ While in the third part of the assessment, the patients were asked about preexisting technical skills, their willingness to use ePRO, and potential barriers in relation to their health status [37], the fourth part concerned with the patients´ evaluation of the ePRO tool (publication in preparation). The patients completed the second part of the assessment both on paper and using a tablet, while they answered the questions in the other parts only in paper-based form.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first part focused on the patientsʼ While in the third part of the assessment, the patients were asked about preexisting technical skills, their willingness to use ePRO, and potential barriers in relation to their health status [37], the fourth part concerned with the patients´ evaluation of the ePRO tool (publication in preparation). The patients completed the second part of the assessment both on paper and using a tablet, while they answered the questions in the other parts only in paper-based form.…”
Section: Methodsmentioning
confidence: 99%
“…Although paperbased surveys of PRO still predominate because there are only a few reliable and validated ePRO questionnaires, numerous projects have evaluated feasibility and acceptance of HRQoL in ePRO measurement in the last few years [29][30][31][32][33][34]. Nevertheless, knowledge regarding patient acceptance, feasibility, and barriers remains limited [35], especially since hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37]. Although studies have already demonstrated a potential equivalence between some paper-based PRO and ePRO, reliability of ePRO questionnaires should be verified so as not to endanger the validity of ePRO surveys [10,[36][37][38][39][40].…”
Section: Electronic Measurement Of Patient-reported Outcomesmentioning
confidence: 99%
See 3 more Smart Citations